The association between infectious burden and Parkinson's disease: A case-control study. Issue 8 (August 2015) - Bu, Xian-Le; Wang, Xin; Xiang, Yang; Shen, Lin-Lin; Wang, Qing-Hua; Liu, Yu-Hui; Jiao, Shu-Sheng; Wang, Ye-Ran; Cao, Hong-Yuan; Yi, Xu; Liu, Cheng-Hui; Deng, Bo; et al.
Abstract: Introduction: The etiology of Parkinson's disease (PD) remains unclear. The aim of this study was to examine the association between common pathogenic infections and PD. Methods: Antibody titers to common infectious pathogens including cytomegalovirus (CMV), Epstein Barr virus (EBV)，herpes simplex virus type-1 (HSV-1), Borrelia burgdorferi ( B. burgdorferi ), Chlamydophila pneumoniae ( C . pneumoniae ) and Helicobacter pylori ( H. pylori ) were measured by ELISA in serum of 131 PD patients and 141 normal controls. Infectious burden (IB) was defined as a composite serologic measure of exposure to these common pathogens. Results: Seropositivities toward zero-two, three-four and five-six of these pathogens were found in 11%, 74% and 15% of normal controls while in 4%, 61% and 35% of PD patients, respectively. IB, bacterial burden and viral burden were independently associated with PD. Schwab and England (S&E) scores were negatively correlated with IB in patients with PD. Serum α-synuclein protein levels and inflammatory cytokines (interleukin-1β and interleukin-6) in individuals with higher IB were also significantly higher. Conclusions: IB consisting of CMV, EBV, HSV-1, B. burgdorferi, C. pneumoniae and H. pylori is associated with PD. This study supports the role of infection in the etiology of PD. Highlights: Higher infectious burden was found in PD patients. Individuals with higher infectious burden had higher alpha-synuclein levels in serum. Subjects with higher infectious burden had higher IL-1beta and IL-6 levels in serum. This study supports the role of infection in the etiology of PD.